The finance of public libraries - Furlong, John T. (Bottom line (New York, N.Y.), 2002)
Although it's been over a year in the making,the timing of the release of this issue of thejournal could not be more appropriate. Therecent economic downturn has left publiclibraries scrambling, to find not only alternativesources for funding, but also proof for taxpayersof the worth of their local libraries.